Translators' Agency in Persian Fansubbed Movies: A Paratextual Analysis - Nima Noushmand; Milad Miraki (Critical Literary Studies)
Drawing upon the notion of ‘paratextual agency’ (Paloposki, “Limits of Freedom” 191), the current study investigated the agency of the Iranian fansubbers. To do so, a corpus of 20 Persian fansubs of Hollywood movies released during the last decade was selected randomly. The study was carried out in two steps. Firstly, translators’ notes were categorized based on their content, frequency, and percentage of each category. Secondly, these notes were analyzed to scrutinize the agency of the Iranian fansubbers. The findings of the study reveal that notes added on the part of the Iranian fansubbers can be categorized into narrative-related notes, locations, famous figures, organizations, medical information, allusions, and transliteration. The study illustrates that by providing such notes to the audience, Iranian fansubbers move beyond the conventional role of subtitler and a mere linguistic conveyor of the movies and take the responsibility of teachers, researchers, cultural representatives, and intermediary agents. The study concludes that fansubbing in Iran is concerned with elucidating culture-bound items of the movies to make them more understandable for the audience. The conclusions of this study can open up prospective avenues for the sociologically-oriented approaches to audiovisual translation, with an eye on the agency and status of fansubbers